THE ART OF TRANSLATION (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article explores translation as a unique type of activity that possesses artistic characteristics. It analyzes the role of thetranslator in intercultural communication, as well as the key concept of translation equivalence, which determines the degree ofcorrespondence between the translation and the original text. It is emphasized that translation is not a mere mechanicalreproduction of the source text but a creative process that requires analytical thinking, a deep understanding of linguisticstructures, and cultural context. The distinction between literal and word-for-word translation is highlighted, along with thenecessity of functional equivalence to achieve translation adequacy. The study examines the impact of linguistic asymmetry on thetranslation process and the need to preserve the stylistic features of the original. The article concludes that translation is not onlythe transfer of meaning from one language to another but also a complex intellectual act based on the translator’s subjectiveperception.